Pelatihan Manajemen Perpustakaan Sekolah dan Pelabelan Buku Perpustakaan - Julita, Delta; Putra, Eka; Bustami, Yuserizal (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
Libraries have a strategic role in building schools, in the era of digitalization it is not only a necessity but a demand for using good library digitization in order to increase competitiveness and increase the excellence of schools, for research purposes, to help SD 07 Padang Leban Elementary School, Tebing Tinggi Village, Ranah Ampek District Hulu Tapan, Pesisir Selatan Regency. This training activity was carried out on July 21-July 23. Which is carried out in 3 stages: 1. Cycle I Stage, namely the Preparation Stage.2. Cycle II stages, namely the Implementation Stages. The final stage, namely the results stage of this research. Data collection methods used in implementing community service programs regarding school library management training regarding the important role of libraries for schools and students. This is in the form of socialization and assistance to schools.